2017
DOI: 10.1183/13993003.02170-2016
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal modelling study estimates acute symptoms of community acquired pneumonia recover to baseline by 10 days

Abstract: Our aims were to address three fundamental questions relating to the symptoms of community-acquired pneumonia (CAP): Do patients completely recover from pneumonia symptoms? How long does this recovery take? Which factors influence symptomatic recovery?We prospectively recruited patients at two hospitals in Liverpool, UK, into a longitudinal, observational cohort study and modelled symptom recovery from CAP. We excluded patients with cancer, immunosuppression or advanced dementia, and those who were intubated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 33 publications
3
38
0
1
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11]. Are the findings of WOOTTON et al [1] generally representative of patients with CAP elsewhere? Is the "new" pathology driving the adverse outcomes truly unrelated to the speed and completeness of resolution of pneumonia, or are we not measuring resolution properly?…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10][11]. Are the findings of WOOTTON et al [1] generally representative of patients with CAP elsewhere? Is the "new" pathology driving the adverse outcomes truly unrelated to the speed and completeness of resolution of pneumonia, or are we not measuring resolution properly?…”
mentioning
confidence: 98%
“…My usual response is a mixture of educated guess and anecdotal experience: "Probably not for 6-8 weeks at leastand it may be longer", mentally reducing that time frame for younger patients and increasing it for the elderly. Given how fundamentally important this question is for our patients, the study in this issue of the journal by WOOTTON et al [1] is particularly welcome. What I am not sure of is whether the study conducted has really answered the question.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The results of this study also demonstrated that, for a number of participants, endurance during physical tasks was reduced even a month after discharge from hospital. It may be hypothesized, based on results of this and other studies [5, 51], that long-term ongoing decrease in overall health status reported by CAP patients is linked to fatigue and reduced endurance for activities of daily living, rather than overall burden of symptoms which appear to return quickly to baseline [3]. Further research is required to fully investigate the role of impaired endurance in poor long-term outcomes from CAP and identify effective interventions to address poor exercise tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Community-acquired pneumonia (CAP) is not only a common cause of death in Australia [1], but also the third leading contributor to lost disability-adjusted life years worldwide, especially in the elderly population [2]. While it is often expected that patients with CAP will return to their pre-pneumonia baseline within a short period of time [3], many continue to suffer from significant deconditioning and loss of functional independence and wellbeing long after diagnosis [4, 5]. Misunderstanding of recovery may in part be due to the common outcome measures used to ascertain the effectiveness of treatment responses, such as time to clinical stability, adverse events, readmissions, and hospital length of stay [610], which largely support the interests of health providers rather than patients [11].…”
Section: Introductionmentioning
confidence: 99%